Ironworking slags from Late Iron Age sites in Hungary - composition, microstructure and function. Issue 13 (2nd October 2020) - Török, Béla; Kristály, Ferenc
ABSTRACT: Numerous slag samples and a piece of iron bloom with slag from excavations of Celtic settlements (La Téne C and D) at Ordacsehi, Szilvásvárad and Jászberény (Hungary) were examined. The main objectives of the investigations were to study the material and structural properties of the slag specimens, the definition of the metallurgical functions of the different pieces of slag. Analytical techniques are wet chemical analysis (ICP-OES complemented with carbon determination, moreover using titration for separating the Fe 2+ and Fe 3+ ), textural-chemical investigations with SEM-EDS microanalysis and mineralogical analysis with XRD. Chemical investigations can be supplemented by ED-XRF. Most of the examined slags can be originated from the purification hammering process, where in an oxidizing atmosphere intended to separate the slag from the iron after reheating the bloom, or the forging of the iron tool. Some of the slag samples with fine dendrites remind metallurgical slag, although there have not been found traces of bloomery at the excavation sites. The examined slaggy bloom-fragment interlocks to the beginning of the technological line of forging as the first (by)product after the smelting formed in the bloomery furnace. Most of the examined slag samples are by-products of smithy workshop working in buildings.